Influence of PCDH9 (rs9540720) and narcissistic personality traits on the incidence of major depressive disorder in Chinese first-year university students: findings from a 2-year cohort study - Xu, Ruixue; Liu, Zhaorui; Li, Hanyun; Luo, Linlin; Zheng, Yi; Mu, Fuqin; Liu, Yujia; Zhang, Weixin; Zhang, Ying; Wang, Jianli; Liu, Yan (Frontiers in Genetics, 2024)
Objective: The objective of this study was to explore the influence of the polymorphism of the protocadherin 9 (PCDH9) gene and the narcissistic personality trait (NPT) on the risk of major depressive disorder (MDD) in Chinese first-year university students. Methods: A 2-year cohort study was conducted among Chinese first-year university students who were enrolled in 2018 from two universities in Shandong Province, China. The snapshot technique was used to detect the genotypes of PCDH9 (rs9540720). The Chinese version of the Composite International Diagnostic Interview was used for the MDD assessment. The NPTs were measured by 11 items based on DSM-IV. Patient Health Questionnaire-9 and the Beck Anxiety Inventory were used to assess depressive and anxiety symptoms, respectively. Logistic regression modeling was carried out to examine the relationship between rs9540720, NPTs, and the incidence of MDD. Results: A total of 5,327 students participated in the baseline and follow-up studies and provided their blood samples. PCDH9 (rs9540720) (ORGG+GA = 2.33, 95% CI: 1.35–4.02) and NPTs (OR5–9 = 2.26, 95% CI: 1.40–3.64) increased the risk of MDD onset. There was no multiplicative interaction between NPTs and Rs9540720 (OR = 1.51, 95% CI: 0.30–7.63). Furthermore, there was no additive interaction between them (RERI = 2.40, 95% CI: –0.82–5.62; AP = 0.47, 95% CI: –0.04–0.97; and S = 2.37, 95% CI: 0.54–10.33). Conclusion:PCDH9 (rs9540720) and more NPTs are the risk factors for the incidence of MDD in Chinese first-year university students.